MODERASI BERAGAMA DI DESA SARANG GITING - Rahmaini Rahmaini; Khairul Amin; Annisa Chairani; Husaini Lutfiah Erdani Sinaga; Gina Sonia Sitepu; Iranida Iranida (STIT AL-AMIN KREO TANGERANG, 2021)
Moderation is a core tenet of Islam. Moderate Islam is a religion which in all respects, religion, customs, ethnicity and the nation themselves, is highly relevant to the environment of diversity. This Islamic moderation can respond to numerous religious and civilisational concerns. The purpose of this study is to find out how religious moderation is in the village of Sarang Gitting, Dolok Masihul sub-district. In this study using (field research), namely observations or observations involved researchers in the field. As well as researchers conducted interviews with the community of the village of nest gitting. The results of this study are that the people of Sarang Gitting Village respect each other, help each other, and protect each other without questioning the differences in beliefs that exist. The two of them are not mutually anarchist and also understand Radicalism. This is what makes the people of the village of Sarang Gitting live a safe and peaceful life.